Performance of agricultural crops under Eucalyptus tereticornis based agroforestry system in semi-arid ecosystem of Haryana - SIROHI, CHHAVI; Kumar, Parvinder; Dhillon, R.S.; Bhardwaj, K.K.; Ahlawat, K.S.; Handa, A.K.; Arunachalam, A.; Kumari, Sushil (Indian Journal of Agroforestry, 2026)
A field experiment was carried out during 2019-20 and 2020-21 to evaluate the crop productivity and light availability under Eucalyptus tereticornis based agrisilviculture system in semi-arid region of Haryana. Clonal eucalypts was established at 8 × 2 m spacing in October 2016, with initial plant height and basal diameter of 48.9 cm and 3.81 mm, respectively. After 3 and 4 years, the trees attained an average height of 16.5 m and 17.8 m, and diameter at breast height (dbh) of 15.5 cm and 17.1 cm, respectively. The experiment was laid out in a randomized block design with three replications, incorporating two Kharif crops (moong and cowpea) and three Rabi crops (wheat, mustard, and berseem) grown in interspaces. Results revealed a significant decline in yield of all intercrops under eucalypts based agroforestry system compared to sole cropping. After attaining the age of three years, the maximum yield reduction was recorded in mustard (27.8%) and cowpea (27.7%), followed by moong (22.8%), wheat (17.3%), and berseem (15.8%). However, the reduction was more pronounced at the age of four years plantation, with cowpea showing the highest decline (36.3%), followed by mustard (32.4%), moong (31.0%), wheat (29.2%), and berseem (25.4%). The decrease in crop productivity was mainly attributed to reduced solar radiation and increased competition for moisture and nutrients. Light measurements indicated a substantial reduction (54.9-61.9%) in available light intensity under eucalypts canopy compared to open conditions, with the highest reduction observed during the Kharif season. The findings suggest that while Eucalyptus tereticornis based agroforestry systems significantly affect intercrop yields due to shading and resource competition, they remain a viable land-use option if appropriate management practices are adopted.